Bioluminescence imaging reveals inhibition of tumor cell proliferation by Alzheimer's amyloid β protein - Zhao Hong; Zhu Jinmin; Cui Kemi; Xu Xiaoyin; O'Brien Megan; Wong Kelvin K; Kesari Santosh; Xia Weiming; Wong Stephen TC (Cancer Cell International, 2009)
Abstract Background Cancer and Alzheimer's disease (AD) are two seemingly distinct diseases and rarely occur simultaneously in patients. To explore molecular determinants differentiating pathogenic routes towards AD or cancer, we investigate the role of amyloid β protein (Aβ) on multiple tumor cell lines that are stably expressing luciferase (human glioblastoma U87; human breast adenocarcinoma MDA-MB231; and mouse melanoma B16F). Results Quantification of the photons emitted from the MDA-MB231 or B16F cells revealed a significant inhibition of cell proliferation by the conditioning media (CM) derived from amyloid precursor protein (APP) over-expressing cells. The inhibition of U87 cells was observed only after the media was conditioned for longer than 2 days with APP over-expressing cells. Conclusion Our results suggest that Aβ plays an inhibitory role in tumor cell proliferation; this effect could depend on the type of tumor cells and amount of Aβ.